"What's Keeping Me Up at Night?" Reflections on the COVID-19 Pandemic in Asia. (15th June 2022) - Mundy, Linda; Kearney, Brendon
Abstract: Objectives: The 2021 Health Technology Assessment International (HTAi) Asia Policy Forum (APF) aimed to explore the challenges and opportunities presented by the global COVID-19 pandemic for health systems and industry in the Asia region, to discuss how HTA changed during the pandemic, and what its role may be moving forward into a postpandemic era. Methods: Discussions during the virtual 2021 APF, informed by a premeeting survey of HTA agencies and industry attendees from the region describing their experience during the pandemic, form the basis of this paper. Results: During the pandemic, regulatory approval for COVID-related technologies was fast-tracked with fewer evidentiary requirements, and little or no HTA being conducted before these technologies were implemented in health systems in the region. "Living HTA" incorporating real-world evidence (RWE) as it was generated became part of the HTA landscape. In comparison, non-COVID technologies experienced regulatory approval and HTA delays. A major concern of APF members was future pandemic preparedness, and to ensure that lessons are learned from COVID-19. Governments need to continue to invest in innovation and allow early regulatory approvals with the increased use of RWE. Capacity building was identified as a key investment, including capacity in HTA, modeling, as well as local production of necessary supplies and equipment. Finally, collaboration at all levels of the health system was viewed as vital. Conclusions: Post-COVID, different forms of HTA must be embraced as part of the new HTA landscape in addition to increased intra- and intercountry collaboration across all sectors of the health system, including regulatory bodies.